2014
DOI: 10.1007/s11423-014-9344-7
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative filtering for expansion of learner’s background knowledge in online language learning: does “top-down” processing improve vocabulary proficiency?

Abstract: In recent years, collaborative filtering, a recommendation algorithm that incorporates a user's data such as interest, has received worldwide attention as an advanced learning support system. However, accurate recommendations along with a user's interest cannot be ideal as an effective learning environment. This study aims to develop and evaluate an online English vocabulary learning system using collaborative filtering that allows learners to learn English vocabulary while expanding their interests. The onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In their study of the effectiveness of collaborative filtering on learners' English vocabulary, Yamada et al (2014) emphasized that their model enabled learners to read articles and score higher on topical vocabulary tests. This 2-month long study showed that with their collaborative model, learners were able to expand their interests while also learning English vocabulary.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In their study of the effectiveness of collaborative filtering on learners' English vocabulary, Yamada et al (2014) emphasized that their model enabled learners to read articles and score higher on topical vocabulary tests. This 2-month long study showed that with their collaborative model, learners were able to expand their interests while also learning English vocabulary.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A learner can demonstrate the acquisition of knowledge and skills as a product of their learning process. Most key studies in this category operationalize affected learning through grades or test scores or scores [29], [33]- [35], [37], [49], [50], [53], [54], [57], [61], [63], [67]- [70], [74]- [76], which is a direct assessment of learning as performance on a task (e.g., an exam or final test) [94]. Although grades may seem to be a direct operational definition, this is debatable.…”
Section: Analysis and Refinement Of The Classification Schemementioning
confidence: 99%
“…Researchers have been applying these resources to learning systems to clarify the effects of recommender systems for learning (e.g., Liang et al, 2006;Chen et al, 2007;Yamada et al, 2014). Many techniques for a recommender system have also been proposed.…”
Section: Introductionmentioning
confidence: 99%